The Degree of Physical Education Teachers’ Use of Alternative Assessment Strategies and its Tools in Albadia Alwosta Schools - Al-Jbour, Aws; Eliwah, Saddam; Alrawashdeh, Mai; Hussein, Abdelsalam (Dirasat: Educational Sciences, 2023)
Objectives: This study assessed the usage degree of physical education teachers of alternative assessment strategies and its tools in Albadia Alwosta schools. Methods: The descriptive approach was used in the current study. A questionnaire consisting of (23) items, divided into six fields of assessment (performance-based, pin and paper, observation, communication, self-feedback and alternative assessment tools) was constructed. After validity and reliability were checked, data were collected from (79) male and female teachers in Albadia Alwosta schools who were selected randomly using a systematic sampling method of the study population (130). The study classified the usage degree into three levels (1.00 – 2.33 low, 2.34 – 3.67 moderate, and 3.68 – 5.00 high). Results: The results showed that the usage degree of physical education teachers of alternative assessment tools and strategies in Albadia Alwosta schools was moderate (3.25 ± 0.54). The observation strategy was the first (4.08 ± 0.79) and pin and paper strategy was the last (2.23 ± 0.53). The results also showed that there were no significant differences between male and female teachers and between teachers of different experiences in these strategies and tools of assessment (P > 0.05). Conclusions: This study may help stakeholders at the Ministry of Education who work at developing educational policies to embed physical education teachers’ manual guide with alternative assessment strategies and tools that suit the educational stage which in turn enhances the education process.